2018
DOI: 10.1016/j.jpainsymman.2018.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Preference for Palliative Care in Cancer Patients: Are Men and Women Alike?

Abstract: Significant gender differences in patients' preferences for palliative care could partially account for gender disparities in end-of-life care. Interventions to promote palliative care among men could reduce these disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
54
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 36 publications
(54 reference statements)
10
54
3
2
Order By: Relevance
“…This corroborates the few studies that have already demonstrated differences in symptom management medication receipt by age, sex, and race/ethnicity, while controlling for symptom severity. 41,42 Although the symptom experience may vary across these dimensions, gaps in access, communication, or even provider bias may also contribute to these patterns. 43,44 The complexity of the relationships between patient symptom experience, reporting to providers, provider prescribing behavior, medication receipt, and adherence highlights the need for further research in these areas.…”
Section: Discussionmentioning
confidence: 99%
“…This corroborates the few studies that have already demonstrated differences in symptom management medication receipt by age, sex, and race/ethnicity, while controlling for symptom severity. 41,42 Although the symptom experience may vary across these dimensions, gaps in access, communication, or even provider bias may also contribute to these patterns. 43,44 The complexity of the relationships between patient symptom experience, reporting to providers, provider prescribing behavior, medication receipt, and adherence highlights the need for further research in these areas.…”
Section: Discussionmentioning
confidence: 99%
“…US-based research has consistently found that women are more likely than men to be enrolled in hospice which is seemingly related to both provider and patient bias. 65 69 Saeed and colleagues 67 found that, among 383 patients with metastatic cancer, women were three times more likely than men to consider palliative care, even when controlling for disease factors, age, race, education and financial strain. The study authors explained the results as follows: there is a societal norm that men are supposed to be tough and invulnerable and there is a lot of vulnerability in seeking help and focusing on comfort care instead of always being in fighter mode.…”
Section: Gender and Hospice And Specialist Palliative Carementioning
confidence: 99%
“…Sex-and gender-considerations are important in both SDM itself and SDM implementation interventions. Sex and gender are important variables for decision making styles, communication styles, and values and preferences-all key issues in SDM [31][32][33][34][35]. Health professionals' sex and gender awareness will also impact their ability to identify risk factors for various illnesses, variables that may affect treatment options and their implications [36].…”
Section: Plos Onementioning
confidence: 99%